The protein kinase promiscuities in the cancer-preventive mechanisms of NSAIDs. Issue 1 (January 2016) - Norvaisas, Povilas; Chan, Diana; Yokoi, Kenji; Dave, Bhuvanesh; Ziemys, Arturas
Abstract : NSAIDs have been observed to have cancer-preventive properties, but the actual mechanism is elusive. We hypothesize that NSAIDs might have an effect through common pathways and targets of anticancer drugs by exploiting promiscuities of anticancer drug targets. Here, we have explored NSAIDs by their structural and pharmacophoric similarities with small anticancer molecules. In-silico analyses have shown a strong similarity between NSAIDs and protein kinase (PK) inhibitors. The calculated affinities of NSAIDs were found to be lower than the affinities of anticancer drugs, but higher than the affinities of compounds that are not specific to PKs. The competitive inhibition model suggests that PK might be inhibited by around 10%, which was confirmed by biochemical screening of some NSAIDs against PKs. NSAIDs did not affect all PKs universally, but had specificities for certain sets of PKs, which differed according to the NSAID. The study revealed potentially new features and mechanisms of NSAIDs that are useful in explaining their role in cancer prevention, which might lead to clinically significant breakthroughs in the future.